Challenges in economic and financial policy formulation an Islamic perspective - Askari, Hossein; Iqbal, Zamir; Mirakhor, Abbas (Palgrave studies in Islamic banking, finance, and economics, 2014)
This exciting new volume addresses the design and implementation of policies in Muslim countries and outlines the all-important question of policy objectives designed and implemented to convert the conventional system into Islamic economic and financial systems as envisaged in the Quran.